Pengaruh Habitat Terhadap Ukuran Populasi Kepiting Bakau ( Scylla serrata ) Di Hutan Mangrove Pantai Utara Pemalang - , ANSORI; , Dr. Erny Poedjirahajoe, MP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mangrove forests have ecologis functions as feeding, spawning, and breeding of marine life one of which is mangrove crab (Scylla serrata). Mangrove rehabilitated area which planted in different year had different habitat characteristic. This study aims (1) to determine mangrove to the crab population size each year zoning with different planting (2) to determine the effect of habitat on the mangrove crab populations size. The data collection was done at five different planting years i.e 2001, 2002, 2003, 2004, 2011. Each planting year is divided into three zones based on the width of the green lane. In every zone creating plots with a size of 5 x 5 m to take the data density of vegetation, water temperature, salinity, dissolved oxygen (DO), depth of the mud, the degree of acidity (pH). Then put 1 x 1 m plots within plots 5 x 5 m to calculate the amount of mud crab. The data analysis used correlation-regression equation. The results showed that the population of mangrove crab in medial zone of the average number of population size is higher by 5583.33 individual/ha, while the lowest population present was in the distal zone. From regression analysis, the predicted regression equation is Y= -0.72 + 0.42 X1+ 0.02 X2 with value r =0,48. This means that population of mangrove crab effected by salinity and and DO.